Cunningham's manual of practical anatomy. Volume three, Head and neck and brain - Romanes, G. J. 1916- (George John) (Cairo : Mass publishing company, 1997)
ompletely redesigned in an attractive new format, this popular three-volume manual provides students and practitioners with a comprehensive guide to human anatomy and a dissection guide recognized throughout the world. For the new edition, the dissection guide has been separated from the text and remodeled to make it more distinctive and easier to read, and the text itself has been greatly expanded, with new sections on embryology, organogenesis, congenital malformations of clinical significance, and the new imaging and diagnostic techniques such as CT scanning. With an expanded general introduction and additional explanations throughout, the new edition will prove the best Manual ever, answering the needs of a wide array of students and courses.
Includes index.
Keywords: Human anatomy; Head -- anatomy; Brain -- anatomy; Neck -- anatomy